Visible Light-Mediated Photochemical Reactions of 2-(2′-Alkenyloxy)cycloalk-2-enones - Graßl, Raphaela (J Org Chem, 2020)
[Image: see text] The title compounds were prepared, and their reactivity was studied upon sensitized irradiation at λ = 420 nm. Thioxanthen-9-one was employed as the sensitizer at a loading of 10 mol % in small-scale reactions and of 2.5 mol % on a larger scale. Cyclohex-2-enones substituted by a 2′-propenyloxy, 2′-butenyloxy, 2′-pentenyloxy, or 2′-methyl-2′-propenyloxy group in the 2-position gave the products of an intramolecular [2 + 2] photocycloadditon. The reaction proceeded with high regioselectivity (crossed product) and perfect diastereoselectivity (nine examples, 34–99% yield). If the olefin in the tether was trisubstituted (3′-methyl-2′-butenyloxy), no cycloaddition was observed. Rather, a cyclization with subsequent hydrogen abstraction occurred (three examples, 65–86% yield). The results are consistent with a reaction course via a triplet enone intermediate and the formation of a 1,4-diradical by an initial cyclization. The analogous cyclopent-2-enones were less prone to an intramolecular reaction. Instead, decomposition or intermolecular [2 + 2] photocycloaddition reactions prevailed. In the latter event, two main products were identified (three examples, 30–43% yield), resulting either from a head-to-head [2 + 2]-photodimerization or from a twofold [2 + 2] photocycloaddition of the enone to the olefin. The latter reaction sequence generated pentacyclic products with a central [1,5]dioxocane ring. The structure assignment of the two product types was corroborated by a single-crystal X-ray analysis.